Shaking Table Tests for Seismic Response of Oblique Overlapped Tunnel - Hao Lei; Honggang Wu; Tianwen Lai (Shock and Vibration)
To study the dynamic response and spectrum characteristics of the three-dimensional crossing tunnel under the action of seismic load, we established a 1/50 downscale model based on a typical of the oblique overlapped tunnel and conducted a series of shaking table tests. Through examining the recorded dynamic responses (acceleration and dynamic strain measured at different locations in model tunnels), we found that the seismic response of the crown was the largest at the central section, and the invert of the tunnels was exactly opposite to the crown, which presented a “parabolic” distribution, and we inferred that the damage within the model may be mainly concentrated on the crown of the tunnels. Additionally, the dynamic strain showed obvious nonlinear and nonstationary characteristics under the action of different degrees of seismic intensities. Different from a single tunnel, the acceleration superposition effect appears in the cross section of two tunnels because of the spatial effect of overlapping tunnels, resulting in the obvious seismic response in the cross section. Meanwhile, we also found that the 1st dominant frequency (0.1–6.26 Hz) seismic wave played a leading role in the process of tunnel slope failure. Furthermore, the analysis of the acceleration response spectrum also showed that the surrounding rock mass has an amplification effect on low-frequency seismic waves. These results help us better understand the features of the dynamic responses and also provide evidence to reinforce the overlapped tunnels against earthquakes.